2013
DOI: 10.1371/journal.pone.0062175
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor (EGFR)-RAS Signaling Pathway in Penile Squamous Cell Carcinoma

Abstract: Penile Squamous Cell Carcinoma (SCC) is a rare cancer with poor prognosis and limited response to conventional chemotherapy. The genetic and epigenetic alterations of Epidermal Growth Factor Receptor (EGFR)-RAS-RAF signaling in penile SCC are unclear. This study aims to investigate four key members of this pathway in penile SCC. We examined the expression of EGFR and RAS-association domain family 1 A (RASSF1A) as well as the mutation status of K-RAS and BRAF in 150 cases of penile SCC. EGFR and RASSF1A express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 32 publications
0
28
1
1
Order By: Relevance
“…In this series, KRAS mutations were found in high grade, advanced tumors, whilst PIK3CA mutations were found in all histological grades. By contrast, in a series of 95 penile cancers testing BRAF and KRAS mutational status, only a single case was found to harbor a KRAS mutation (Gou et al, ). In our study, somatic mutations were identified in 3/10 in situ SCC and in 19/65 (29%) of invasive SCC, while normal tissues were all wt.…”
Section: Discussionmentioning
confidence: 95%
“…In this series, KRAS mutations were found in high grade, advanced tumors, whilst PIK3CA mutations were found in all histological grades. By contrast, in a series of 95 penile cancers testing BRAF and KRAS mutational status, only a single case was found to harbor a KRAS mutation (Gou et al, ). In our study, somatic mutations were identified in 3/10 in situ SCC and in 19/65 (29%) of invasive SCC, while normal tissues were all wt.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, single biomarker predictor models often have limited power to predict cancer patient survival [26][28]. Therefore, the three-gene signature discovered in the present study, which is comprised of molecules within the EGFR/ERK/Fascin signaling pathway, may represent a useful preclinical model for improving ESCC treatment and clinical outcome.…”
Section: Discussionmentioning
confidence: 97%
“…In a literature review of individual data of 28 patients with advanced penile cancer receiving anti-EGFR monoclonal antibodies (cetuximab, panitumumab, and nimotuzumab), a 50% radiological response rate was achieved, but a median PFS of only approximately 3 months (interquartile range, 1.5–5.78, Di Lorenzo et al, 2015). From a biological perspective, EGFR appears a promising target in penile cancer, as it is universally expressed and frequently phosphorylated (Di Lorenzo et al, 2013a), but infrequently amplified (Di Lorenzo et al, 2013a), or mutated (Di Lorenzo et al, 2013b), while mutations of downstream signaling proteins (such as KRAS/BRAF) are rare (Gou et al, 2013). Nevertheless, we failed to identify a signal of prolonged OS associated with the use of cetuximab in our study cohort.…”
Section: Discussionmentioning
confidence: 99%